Приморський регіон: суть та підходи до визначення - Страчкова, Наталя; Strachkova, Natalya (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Вивчено й узагальнено вітчизняний та зарубіжний досвід до визначення суті приморського регіону, виділено основні підходи до визначення приморського регіону в контексті завдань управління та конкретно- наукових досліджень (територіальний та просторовий підходи), надано їх критичний аналіз. Запропоновано визначення приморського регіону з позицій глобального підходу, акцентуючи увагу передусім на системно- функціональних властивостях. Виділено об’єктивні закономірності функціонування приморського регіону в умовах глобалізації. Isolated and generalized national and international experience to the definition of the essence of the seaside region. Identified approaches to determining the maritime region in the context of management objectives and specific research − territorial, based on the characteristics of the formation of the seaside region and spatial taking into account the properties of the economic complex of the coastal region, carried out their critique. A definition of the seaside region from the standpoint of a global approach taking into account the systemic-functional properties under the influence of intense trans-regional flows in boundary communication skills. Identified patterns of functioning maritime region in the context of globalization – a systematic and synergetic, stage-evolutionary dichotomous and dialectical character, the territorial integrity of the spatial, functional component and structural-sectoral forms, hierarchical spatial structures, the multiplicative conditioning.
The Coastal REGION: the Nature and Approaches to the Definition
Keywords: глобалізація; приморський регіон; рубіжна комунікативність; транскордонність; глобальний підхід; globalization; the coastal region; boundary communication skills; cross-border; global approach